(untitled) (Revista Electrónica REDINE, 2023)
Educational organizations require a change in the way management processes are currently carried out; especially, from an emotional point of view, considering that people, in addition to being rational beings, are also emotional. For this reason, emotional intelligence is an important part of the actions of the educational manager, since through its elements such as: self-awareness, self-motivation and empathy, they will develop effective managerial work with the personnel under their charge; Therefore, the teacher who exercises this function is required to become a manager open to change, who knows how to manage his or her emotions appropriately; especially in the exercise of your position, since this knowledge will help you maintain an environment of peace in the organization and carry out your work effectively. Therefore, you need to understand and apply emotional intelligence to channel it effectively; hence, its importance for the educational manager, because by controlling his emotions at the right time, he will be able to effectively manage emotional intelligence. It is in this theoretical context that this essay arises, whose purpose is to analyze self-awareness, self-motivation and empathy as elements of emotional intelligence for the success of educational management.